An experimental test of a greenwashing inoculation intervention: Effects on identification, trust and intentions - Shane Timmons; Ava Whelan; Claire Kelly (The Economic and Social Research Institute (ESRI), 2023)
Misleading claims about the environmental performance of a product or service (i.e. "greenwashing) hinders consumers from making informed choices and penalises genuinely sustainable companies. We pre-tested a greenwashing inoculation intervention using a student sample (N = 206) and then ran a pre-registered replication using a nationally representative sample (N = 2,000). Participants were randomised to learn about greenwashing and ways to identify it or to read more generally about climate change. They then judged six real advertisements (three greenwashed and three that made genuine environmental claims) on whether they were greenwashed, their trust in the brand and their willingness to purchase from the brand. The intervention increased greenwashing ratings to two of the three greenwashed advertisements, with corresponding decreases in brand trust and purchase intentions. The unaffected greenwashed advertisement was for a dairy-free milk alternative from a familiar brand, suggesting that familiarity and product sustainability may counteract greenwashing interventions. However, participants also judged two of the three genuine advertisements as greenwashed, implying a broadly-applied scepticism of environmental claims, particularly towards unfamiliar brands. Despite difficulty distinguishing between greenwashed and genuine advertisements, participants were more confident in their ability to identify greenwashing and had stronger resolves to act in pro-environmental ways in the future. The findings have implication for policy to address the harms of greenwashing.
Keywords: 330